Wushenziye Formula Inhibits Pancreatic β Cell Apoptosis in Type 2 Diabetes Mellitus via MEK-ERK-Caspase-3 Signaling Pathway. (25th September 2018) - Tian, Chunyu; Chang, Hong; La, Xiaojin; Li, Ji-an; Ma, Leilei
Abstract : Background . Wushenziye formula (WSZYF), composed of Radix Polygoni Multiflori Preparata, Mori fructus, Mori folium, and Cassiae semen, is effective in the treatment of type 2 diabetes mellitus (T2DM). Aim . In this study, we aimed to explore the effects and the underlying mechanisms of WSZYF on inhibiting pancreatic β cell apoptosis and improving insulin resistance (IR) in T2DM. Methods . A T2DM model was induced by Goto-Kakizaki diabetes prone rats. Cell apoptosis model was induced in MIN6 cells. Results . In vivo, WSZYF decreased fasting blood glucose (FBG), insulin concentration, insulin resistance index, triglyceride (TG), total cholesterol (TC), and free fatty acids (FFA) in T2DM rats. Meanwhile, WSZYF ameliorated impairments in the morphology and structure of pancreatic tissues. In vitro, WSZYF enhanced cell viability and promoted insulin secretion in the apoptosis model of MIN6 cells. Furthermore, WSZYF modulated the expressions of apoptosis-related molecules by increasing the expressions of MEK1/2, p-MEK1/2, ERK1/2, and p-ERK1/2 and decreasing the cleaved-caspase-3 expression. Conclusion . These findings indicate that WSZYF may become a new drug candidate in the treatment of T2DM and its antidiabetic mechanism is probably inhibiting pancreatic β cell apoptosis by modulating the MEK-ERK-Caspase-3 signaling pathway.